Empiric vs Preemptive Antifungal Strategy in High-Risk Neutropenic Patients on Fluconazole Prophylaxis: A Randomized Trial of the European Organization for Research and Treatment of Cancer. (30th July 2022) - Maertens, Johan; Lodewyck, Tom; Donnelly, J Peter; Chantepie, Sylvain; Robin, Christine; Blijlevens, Nicole; Turlure, Pascal; Selleslag, Dominik; Baron, Frédéric; Aoun, Mickael; Heinz, Werner J; Bertz, Hartmut; et al.
Abstract: Background: Empiric antifungal therapy is considered the standard of care for high-risk neutropenic patients with persistent fever. The impact of a preemptive, diagnostic-driven approach based on galactomannan screening and chest computed tomography scan on demand on survival and on the risk of invasive fungal disease (IFD) during the first weeks of high-risk neutropenia is unknown. Methods: Patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) and allogeneic hematopoietic cell transplant recipients were randomly assigned to receive caspofungin empirically (arm A) or preemptively (arm B), while receiving fluconazole 400 mg daily prophylactically. The primary end point of this noninferiority study was overall survival (OS) 42 days after randomization. Results: Of 556 patients recruited, 549 were eligible: 275 in arm A and 274 in arm B. Eighty percent of the patients had AML or MDS requiring high-dose chemotherapy, and 93% of them were in the first induction phase. At day 42, the OS was not inferior in arm B (96.7%; 95% confidence interval [CI], 93.8%–98.3%) when compared with arm A (93.1%; 95% CI, 89.3%–95.5%). The rates of IFDs at day 84 were not significantly different, 7.7% (95% CI, 4.5%–10.8%) in arm B vs 6.6% (95% CI, 3.6%–9.5%) in arm A. The rate of patients who received caspofungin was significantly lower in arm B (27%) than in arm A (63%; P < .001). Conclusions: The preemptive antifungal strategy was safe for high-risk neutropenic patients given fluconazole as prophylaxis, halving the number of patients receiving antifungals without excess mortality or IFDs. Clinical Trials Registration. NCT01288378; EudraCT 2010-020814-27. Abstract : The initiation of antifungal therapy with caspofungin based on serum galactomannan screening and computed tomography scan when required in profound and prolonged neutropenic patients given fluconazole prophylaxis was found to be noninferior to a fever-driven empiric approach.